2022
DOI: 10.1186/s13148-022-01250-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin accessibility and transcriptome integrative analysis revealed AP-1-mediated genes potentially modulate histopathology features in psoriasis

Abstract: Background Psoriasis is a chronic and hyperproliferative skin disease featured by hyperkeratosis with parakeratosis, Munro micro-abscess, elongation of rete pegs, granulosa thinning, and lymphocyte infiltration. We previously profiled gene expression and chromatin accessibility of psoriatic skins by transcriptome sequencing and ATAC-seq. However, integrating both of these datasets to unravel gene expression regulation is lacking. Here, we integrated transcriptome and ATAC-seq of the same psoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Earlier, we performed genome-wide DNA methylation for psoriatic peripheral blood mononuclear cell samples and psoriatic lesions, identified nine differentially methylated sites (DMSs) strongly related to psoriasis, and interrogated transcriptome to verify the expression of DMS-related genes ( 16 ). In the following research, we found differences in chromatin accessibility and gene expression in different pathological changes of psoriasis ( 5 ). At the same time, a study shows that DNA methylation analysis combined with gene expression displayed a discordant difference in monozygotic twins psoriasis ( 17 ).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Earlier, we performed genome-wide DNA methylation for psoriatic peripheral blood mononuclear cell samples and psoriatic lesions, identified nine differentially methylated sites (DMSs) strongly related to psoriasis, and interrogated transcriptome to verify the expression of DMS-related genes ( 16 ). In the following research, we found differences in chromatin accessibility and gene expression in different pathological changes of psoriasis ( 5 ). At the same time, a study shows that DNA methylation analysis combined with gene expression displayed a discordant difference in monozygotic twins psoriasis ( 17 ).…”
Section: Introductionmentioning
confidence: 78%
“…Typical histopathological traits of psoriasis include hyperkeratosis with parakeratosis, immune cell infiltration, Munro’s microabscess, acanthosis thickening, vascular dilatation congestion, elongation of rete pegs, and granulosa thinning ( 1 ). In our previous studies, we explored the transcriptome ( 3 ) and chromatin accessibility patterns ( 4 ) in psoriatic lesions, and further data mining suggested that each pathological feature might be affected by both transcription and chromatin accessibilities, thus supporting the notion that these kinds of molecular changes would be involved in modulating the epidermal microenvironment ( 5 ). Munro’s microabscess is a characteristic pathological hallmark of early psoriasis, with inflammation encompassing polymorphonuclear leukocytes and forming within the skin’s epidermal layer, which can further trigger the following immune response in the surrounding microenvironment ( 6 8 ).…”
Section: Introductionmentioning
confidence: 82%
“…As the fate-determining regulatory molecule, activator protein 1 or AP-1 transcription factor facilitates the generation of AT2 cells from secretory epithelial cells 12 by remodeling the chromatin-an epigenetic process that confers reduced or increased accessibility to certain parts of the DNA. 17 The epigenetic effects of AP-1 upregulation in RBPJ-knockdown secretory epithelial cells were unraveled by a molecular technique known as an assay for transposase-accessible chromatin using sequencing (ATAC-seq) which uses Tn5 transposases to detect regions of increased accessibility or high transcriptional activity within the chromatin. 18 In short, the Matrigel-based hLO developed by Choi et al can be regarded as a successor to the model designed by Byrd and Brainson, which was capable of delivering an illustrative epigenetic picture of airway development in damaged adult alveoli.…”
Section: Accessibility Determines Cell Fate In Alveolar Regenerationmentioning
confidence: 99%
“…However, the genetic factors causing these features are largely overlooked. To identify genes that contribute to or regulate psoriasis-specific histopathological features, a binding and expression target analysis (BETA) was performed on a cohort of 60 skin biopsies (including 20 lesional, 20 non-lesional, and 20 controls) [ 57 ]. Several upregulated genes were linked with chromatin accessibility, and it was found that transcription factor AP-1 regulated increased expression of some of these genes (SQLE, STRN, E1F4, and MYO1B).…”
Section: Large Cohort Transcriptome Analysis Of Psoriasismentioning
confidence: 99%
“…Increased chromatin accessibility facilitated the binding of AP-1 to these target genes and induced their expression. This increased expression of these genes correlated with hyperkeratosis, parakeratosis, and acanthosis thickening in patients [ 57 ].…”
Section: Large Cohort Transcriptome Analysis Of Psoriasismentioning
confidence: 99%